PENGGUNAAN ADVERBIA BAHASA INDONESIA DALAM MEDIA CETAK LOKAL DI KOTA PADANG: KAJIAN MORFOLOGIS DAN SINTAKSIS - Noviatri Noviatri; Aslinda Aslinda (Universitas Andalas, 2020)
The writing of this paper is motivated by the phenomenon of the use of adverb in print media, especially in local newspapers in the city of Padang. The use of adverb, shows the diversity of forms with different behaviors. In this connection, this study aims to describe the forms of adverb used in local print media in the city of Padang and explain their morphological, syntactic and semantic behavior. There are three research methods and techniques used in this paper, 1) data supply methods and techniques, 2) data analysis methods and techniques, and 3) data analysis methods and techniques. The population of this study is the entire use of adverb in local newspapers in the city of Padang. The research sample is adverb used in two newspapers, the Padang Ekspres newspaper and the Haluan newspaper. Based on its shape, there are two forms of adverb used in local newspapers, namely monomorfemis and polymorphemic adverbs. Based on the behavior, the adverbs used in local newspapers have different behavior. Keywords: Adverb, newspaper, forms, behavior